PENGARUH KEPEMILIKAN MANAJERIAL, KEPEMILIKAN INSTITUSIONAL, KOMISARIS INDEPENDEN TERHADAP KINERJA KEUANGAN PERUSAHAAN (UNIB Press, 2025)
Testing and analyzing the influence of managerial, institusional ownership and the existence of an independent board of commissioners on the financial performance of companies listed on the Indonesia Stock Exchange in the infrastructure sector around the 2018-2022 period is the main objective of this research. This research is a type of quantitative research using secondary data where data is obtained from financial reports and annual reports of Infrastructure sector companies that are registered on the Indonesia Stock Exchange where these reports can be accessed via the company’s official website or on the official IDX website. Infrastructure sector companies listed on the IDX are the population of this research. Then samples will be taken using a purposive sampling method which uses several criteria so that 70 samples are obtained in this research. Descriptive statistical analysis, classical assumption testing (normality, multicollinearity, heterodasticity and autocorrelation, multiple regression analysis, and hypothesis testing (determination coefficient, t and F tests) are the data analysis techniques that will be used in this research. The result obtained in research are that managerial and institusional ownership has an influence on the company’s financial performance, but the independent board of commissioners has on influence on the company’s financial performance.